Pengaruh Pola Asuh Terhadap Kemandirian Belajar Anak Usia Dini Dimasa Pandemi Covid 19 - Laela; Supriyadi (Arden Jaya Publisher, 2022)
This study aims to reveal Parenting Parenting (X) on the independence of early childhood learning (Y). This research uses quantitative research with a survey approach. The study was conducted on children aged 5-6 years KB Dewi Kania. The sampling technique used stage random sampling. The research sample amounted to 30 Early Childhood Education. Collecting data using valid and reliable instruments. Data analysis using simple regression. The conclusion of the research revealed: (1) Linear Regression Equation Y-17.507+0.348X (2) Parental Parenting has a positive effect on independent learning in early childhood (3) The significance test obtained that the regression line equation F hit is smaller than 0.05, thus, the Yor X regression is significant or parenting style affects the learning independence of early childhood (4) The correlation coefficient (xy)-0.122 and Fhit (Fchange) 6.547, with a p-value less than 0.05. Thus, the correlation coefficients of X and Y are meaningful or significant. The coefficient of determination is 0.144, which means that 14.4% of the variation in the variable of early childhood learning independence is influenced by parenting patterns.